Human papillomavirus genotypes in cervicitis and atypical squamous cell of undetermined significance lesions among women in Erbil, Iraq: Human Papillomavirus Genotypes in Cervicitis and ASCUS Lesions Among Women in Erbil, Iraq - Hamad ameen, Dashty; Hushair Salim , Tavga (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: Human papillomavirus infection is known to be the primary reason for cervical carcinoma. Steady infection with high risk (HR)-HPV strains is behind most abnormal cervical lesions, this studyaims to investigate the prevalence and genotype distribution of HPV in cervical samples from women between 20 to 50 years old with different cervical lesions, including cervicitis and atypical squamous cells of undetermined significance (ASC-US) cases. Methods: Cervical smears of 113 patients diagnosed with atypical squamous cell of undetermined significance and cervicitis were included in the study and examined for HPV detection used reverse transcription polymerase chain reaction and hybridization method, followed by HPV genotyping assay specimens Results: Out of the total 113 cases, 24.74% were positive for HPV infection, and 75.22% were negative for HPV infection. Most of the patients diagnosed with cervicitis were within 35-39 age group, accounting for 26.3% of the total cases. In contrast, most patients with ASCUS were in the 30-34 age group, representing 29.7%. The majority of patients exhibit a single serotype (60.7%), while multiple serotypes were found in 39.3%. HR-HPV16 and multiple genotype HPV (31,35,39,51,52,56,58,59,66, and 68) were the most frequently identified genotypes. Conclusion: The detection of both low- and HR- HPV genotypes were reported and not uncommon among patients with cervicitis and a typical squamous cell of undetermined significance. High risk (HR)-HPV16 and multiple genotypes were the most frequently diagnosed by PCR test. Consequently, it is highly advisable to create a program for cervical cancer screening and prophylactic HPV vaccination for early diagnosis and prevention of cervical abnormalities and neoplasia in Iraq.